Respuesta :

Answer:

D

Step-by-step explanation:

Using the rules of logarithms

log x - log y = log ([tex]\frac{x}{y}[/tex] )

log [tex]x^{n}[/tex] = nlog x

[tex]log_{b}[/tex] x = n ⇒ x = [tex]b^{n}[/tex]

Given

[tex]log_{3}[/tex] (4x) - 2[tex]log_{3}[/tex] x = 2

[tex]log_{3}[/tex] (4x) - [tex]log_{3}[/tex] x² = 2

[tex]log_{3}[/tex] ([tex]\frac{4x}{x^2}[/tex] ) = 2

[tex]log_{3}[/tex] ([tex]\frac{4}{x}[/tex] ) = 2

[tex]\frac{4}{x}[/tex] = 3² = 9 ( multiply both sides by x )

4 = 9x ( divide both sides by 9 )

[tex]\frac{4}{9}[/tex] = x → D